The Influence of the Talking Stick Learning Model on the Critical Thinking Skills of Grade IV Students in Science Learning at UPTD SD Negeri 122345 Pematangsiantar - Sianipar, Arjun; Siagian, Asister Fernando; Sitohang, Sukardo (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to determine the effect of the Talking Stick learning model on the critical thinking skills of fourth-grade students in Natural Sciences (IPA) at the UPTD of State Elementary School 122345 Pematangsiantar. The method used is quantitative with a One-Group Pretest-Posttest design involving 30 students as a sample. The research instrument is an essay question that has been validated by two validators using the Aiken's V formula, with high validity results in the aspects of content, construct, and language. Data on students' critical thinking skills were collected through pretests and posttests, then analyzed using normality tests, homogeneity tests, and N-Gain tests. The results showed a significant increase in students' critical thinking skills after the application of the Talking Stick model, with an average pretest score of 44.86 and a posttest score of 88.83. The average N-Gain score of 0.79 (high category) indicates the effectiveness of this learning model in improving critical thinking skills. The application of the Talking Stick model has also been shown to increase student engagement, motivation, and activity in learning. In conclusion, the Talking Stick learning model is effective in improving the critical thinking skills of fourth grade students and is recommended for wider application to support active, enjoyable, and meaningful learning.